ANALISIS DETERMINAN STRUKTUR, PERILAKU DAN KINERJA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2015)
This study discusses the market structure, conduct, performance (SPK) Islamic banking industry as well as the enforceability SPK Islamic banking industry. Variables include the study of concentration, market share, advertising intensity, the level of financing, financing problems, capital intensity, and the performance of the Islamic banking industry include profitability and operational efficiency, as well as variable dummy macro economic conditions. Source data from the financial statements of Islamic banking, and financial statements of four foreign Islamic banks, namely Bank Syariah Mandiri, Bank Muamalat Indonesia, Bank Mega Sraiah, and BNI Syariah. The technique of multiple regression analysis using panel data. The results showed that the market structure of the Islamic banking industry is an oligopoly 2005-2014 period. But in the meantime, there has been a change in the structure of the full oligopoly (2005-2008), a tight oligopoly (2009-2012) and became a monopolistic competition (2013-2014) due to the emergence of new Islamic banks in 2010 up to 2015 amounted to Islamic banks 12. Determinants of real influence on the market share structure is variable and intensity behavioral advertising. Advertising will increase the intensity and the concentration of market share. Perikalanan intensity intensive Islamic banks classified about 25 percent. That is about a quarter of the income allocated to the cost of promotion and advertising. Advertising intensity can improve the structure and market share. Advertising determinants that influence the behavior of Islamic banks is capital intensity, market share, concentration and interaction of market share, expansion financing and capital intensity. SCP variable relationships in the study of Islamic banking industry in Indonesia were tested empirically is the hypothesis of efficiency. Profit performance of the banking industry was not caused by the structure of sharia concentrated or collusion of the oligopoly but because of its efficiency. Keywords: concentration, market share, promotion intensity, profitability.